Efeito do retratamento endodôntico sobre a resistência de união de cimentos resinosos à dentina intrarradicular - Pereira, Kamila de Figueiredo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The aim of this study was to evaluate the effect of endodontic retreatment on the bond strength and the penetrability of different cementing systems of fiberglass posts to root dentin through the push out bond strength, confocal laser microscopy and scanning electron microscopy. Sixty human teeth with single canals and ovalshaped were used (n=15): ETA - Endodontic treatment and cementation with RelyX ARC; ETU - Endodontic treatment and cementation U200; ERA - Endodontic retreatment and cementation RelyX ARC; ERU - Endodontic retreatment and cementation with U200. The groups with conventional endodontic treatment were filled with AH plus (ETA and ETU) and the groups that suffered endodontic retreatment were filled, primarily, with Endofill and, after, with AH Plus.  The fiber glass posts received as a previous treatment, an alcohol 70% cleaning and application of silane. The groups ETA and ERA received adhesive application. For analysis in confocal laser microscope, were added to the primer adhesive system and the self-adhesive cement, the fluorescent dye rhodamine B isothiocyanate RITC 0.01%. Each root third passed for the push-out test, with a speed of 0.5 mm / min and to verify the penetration and adaptation of the cement in the root dentin analysis were made under confocal laser scanning microscopy. Subsequently each of the specimens were analyzed in scanning electron microscopy, the failures were classified (AD) adhesive; (MI) mixed and (CO) cohesive. For statistical analysis of the results, were selected two criteria: the tests two-way ANOVA and the Tukey test (α <0.05). As a result for push out bond strength ETA showed higher bond strength to radicular dentin than the other groups (p < 0.05) in all radicular thirds. Endodontic retreatment interfered negatively on the penetrability and on the push out bond strength of RelyX ARC and U200 cements to dentin, regardless of the analyzed radicular third.

O objetivo deste estudo foi verificar o efeito do retratamento endodôntico sobre a resistência de união e a penetrabilidade de diferentes sistemas de cimentação de pinos de fibra de vidro à dentina intrarradicular por meio de ensaio mecânico push out, microscopia confocal a laser e microscopia eletrônica de varredura. Foram utilizadas 60 raízes unirradiculares ovaladas de dentes humanos (n=15): ETA -Tratamento endodôntico e cimentação com RelyX ARC; ETU - Tratamento endodôntico e cimentação com U200; ERA - Retratamento endodôntico e cimentação com RelyX ARC; ERU - Retratamento endodôntico e cimentação com U200. Os grupos com tratamento endodôntico convencional foram obturados com AH plus (ETA e ETU) e os grupos que sofreram retratamento endodôntico foram obturados primeiramente com Endofill e após com AH Plus. Os pinos de fibra de vidro receberam como tratamento prévio à cimentação a limpeza com álcool 70%, aplicação de silano e para os grupos ETA e ERA aplicação de adesivo. Para análise em microscópio confocal a laser, foi adicionado ao primer do sistema adesivo e ao cimento autoadesivo o corante fluorescente rodamina B isotiocianato RITC 0,01%. Cada terço radicular foi submetido ao teste de push-out com velocidade de 0,5 mm/min e para verificar a área de adesão e para determinação da penetração e adaptação do cimento na dentina radicular foi feita analise sob microscopia confocal a laser. Na sequência cada um dos espécimes foi analisado em microscopia eletrônica de varredura, as falhas foram classificadas com (AD) adesiva; (MI) mista e (CO) coesiva. Para análise estatística dos resultados foram selecionados os testes ANOVA a dois critérios fixos e Tukey (α<0,05). Como resultado o grupo ETA apresentou maiores valores de resistência de união à dentina intrarradicular que os outros grupos (p<0,05), em todos os terços radiculares ((Resumo completo, clicar acesso eletrônico abaixo).
Keywords: Canal radicular - Tratamento; Força compressiva; Cimentos dentários; Adesivos dentinários; Pinos dentários